2018
DOI: 10.1155/2018/6750217
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Changes of Enamel Produced by Sodium Fluoride, Hydroxyapatite, Er:YAG Laser, and Combined Treatments

Abstract: Occlusal pits and fissures of permanent molars are considered to have higher risk of developing caries. Enamel demineralization can be prevented by applying remineralizing agents, and their absorption increases with prior irradiation. This work evaluates the chemical changes produced by treating occlusal surfaces with sodium fluoride (NaF), hydroxyapatite-NaF-xylitol (HA-NaF-X), Er:YAG laser irradiation (L), and combinations thereof. Fifty enamel samples were randomly assigned to five groups (n = 10): NaF, HA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…14,25 This reduction has been attributed to the surface temperature achieved during enamel laser irradiation, and loss of water and carbonate. 26 In the current study, the selected parameters (low energy density -12.7 J/cm 2 ; pulse energy -100 mJ; frequency -10 Hz; pulse duration -250-400 μs, and water irrigation -5.0 mL/min) were based on previous studies 16,21 and the results of a pilot study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,25 This reduction has been attributed to the surface temperature achieved during enamel laser irradiation, and loss of water and carbonate. 26 In the current study, the selected parameters (low energy density -12.7 J/cm 2 ; pulse energy -100 mJ; frequency -10 Hz; pulse duration -250-400 μs, and water irrigation -5.0 mL/min) were based on previous studies 16,21 and the results of a pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study reported an increase in the Ca/P ratio under similar conditions for treatments with L+NaF, L+HA-NaF-X, L, and NaF, in decreasing order. 21 However, Comar et al 11 reported that fluoride paste (0.2% NaF) is still the best option for reducing dental demineralization in vitro when compared to HA, CPP-ACP and CPP-ACPF. The use of lasers in combination with CPP-ACPF and HA-NaF-X showed a superior performance, which was a promising result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Ceballos-Jiménez et al, (38) compared sodium fluoride (NaF) Er: YAG laser irradiation (L), hydroxyapatite-NaF-xylitol, and combinations of laser with each agent and found a significant increase in the elements and the Ca/P ratio between the study groups with the maximum increase in laser + NaF group. Their results revealed that the application of 1.1% NaF gel on permanent teeth produced a significant increase in F at% in the dental structure leading to a stable Ca/P ratio.…”
Section: Discussionmentioning
confidence: 99%